Effect of Oregano aromatic water supplementation to rumen fluid on in vitro digestion and rumen parameters of starter in calves - OZKAYA, S (The Indian Journal of Animal Sciences, 2020)
Restriction on the use of antibiotics in animal nutrition has led researchers and consumers to use alternative antimicrobial agents. Aromatic plants and their essential oils are one of the alternatives. In the literature, there are studies on the effects of essential oils on in vitro digestion and rumen parameters; however, no studies on the effects of aromatic water, a by-product, have been found. Therefore, this study aims to determine the effects of Oregano aromatic water (OAW) supplemented in 0, 40, 60 and 80 ml/L on in vitro digestion and rumen parameters of starter in calves (n=6 for each doses). The rumen fluid used in the study was obtained from calves of 60 d-age. Total gas and methane gas production, metabolic energy and organic matter digestion were determined by the in vitro gas production technique and the effects on rumen essential oils were observed. The effect of supplemented OAW doses on in vitro gas production, methane production, organic matter digestion, and metabolic energy level was not found to be significant. However, total volatile acids (VFA), acetate (AA), propionate (PA) and butyrate (BA) values and proportions were affected by OAW doses. The findings of the study showed that supplementation of OAW might be useful in modifying rumen fermentation in ruminants.